2018
DOI: 10.1186/s11782-018-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Production risk caused by human factors: a multiple case study of thermal power plants

Abstract: Introduction: Thermal power plants are very popular in China. However, there has not been proportional research attention paid to production risk in these plants and human impact on production due to their importance in electricity generation. This study investigates production risks caused by human factors in thermal power plants and management methods to address identified human factors. Case description: Eighteen semi-structured interviews with front-line, middle and senior managers from four thermal power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Meta-analysis of human factors could help improve employee performance in power plants [10]. Similarly, human factors have been analyzed in terms of the risks faced by thermal power plants' maintenance staff [11]. This analysis showed that, to minimize such errors, understanding human behavior is imperative.…”
Section: Human Factorsmentioning
confidence: 99%
“…Meta-analysis of human factors could help improve employee performance in power plants [10]. Similarly, human factors have been analyzed in terms of the risks faced by thermal power plants' maintenance staff [11]. This analysis showed that, to minimize such errors, understanding human behavior is imperative.…”
Section: Human Factorsmentioning
confidence: 99%
“…Poor performance in the industrial sector, especially in the electricity sector, negatively affects the power plant and contributes to the increase in human errors and the weakness of human factors [5]. The literature confirms the need to conduct more studies and investigations related to the performance shaping factors, including the human performance, human factors, and human error in maintaining thermal and gas power plants [6][7][8][9][10][11][12]. Additionally, further investigation regarding the CSFs of energy management is required [13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, PSFs, especially human factors, can improve the personnel's behavior performance toward EMP in power plants [ 7 ]. The poor performance of PSFs in power plants has resulted in increased human errors, which can have long-term negative effects [ [8] , [9] , [10] , [11] , [12] , [13] ]. Furthermore, unlike nuclear power generation systems that require high levels of automation, thermal power plants typically operate with lower levels of automation.…”
Section: Introductionmentioning
confidence: 99%